A dynamical analysis of the Taurid Complex: evidence for past orbital convergences. Issue 2 (4th August 2021) - Egal, A; Wiegert, P; Brown, P G; Spurný, P; Borovička, J; Valsecchi, G B
ABSTRACT: The goal of this work is to determine if the dynamics of individual Taurid Complex (TC) objects are consistent with the formation of the complex via fragmentation of a larger body, or if the current orbital affinities between the TC members result from other dynamical processes. To this end, the orbital similarity through the time of comet 2P/Encke, 51 near-Earth asteroids (NEAs), and 16 Taurid fireballs was explored. Clones of each body were numerically simulated backwards in time, and epochs when significant fractions of the clones of any two bodies approached each other with both a low Minimum Orbit Intersection Distance and small relative velocity were identified. Only 12 pairs of bodies in our sample show such an association in the past 20 000 yr, primarily circa 3200 BCE. These include 2P/Encke and NEAs 2004 TG10, 2005 TF50, 2005 UR, 2015 TX24, and several Southern Taurid fireballs. We find this orbital convergence to be compatible with the fragmentation of a large parent body 5000–6000 yr ago, resulting in the separation of 2P/Encke and several NEAs associated with the TC, as well as some larger meteoroids now recorded in the Taurid stream. However, the influence of purely dynamical processes may offer an alternative explanation for this orbital rapprochement without requiring a common origin between these objects. In order to discriminate between these two hypotheses, future spectral surveys of the TC asteroids are required.